Synthesis and Analytical Studies of a New Bis-azo Dye: 2,6-Bis(9-hydroxyphenanthryl-10-azo) pyridine - SINGH, ISHWAR; K. SHARMA, ASHOK; K. YADAV, SANJIV; SINGH, DEVENDER; DO HAN, SANG (Asian Journal of Chemistry, 2010)
A new pyridyl bis-azo dye, 2,6-bis(9-bydroxypbclWltbryl-10-azo) pyridine has been synthesized and proposed as a sensitive chromogenic reagent for the determination of copper, cobalt, zinc and cadmium. The molar absorptivities are 5.8 x 104 L mole-1 cm-1 at 556 nm for copper, 4.7 X 104 L mole-1 cm-1 at 540 nm for cobalt, 6.4 X 104 L mole-1 cm-1 at 556 nm for zinc and 6.0 X 104 L mole-1 cm-1 at 560 nm for cadmium. Other pbysico-chemical characteristics bave been established spectrophotometrically. Trace levels of copper in some foodstuffs bave been determined with the reagent.